2010
DOI: 10.1590/s0100-29452010005000101
|View full text |Cite
|
Sign up to set email alerts
|

Interação enxerto e porta-enxerto na incidência da resinose do cajueiro

Abstract: RESUMO -A expansão do cajueiro-anão-precoce no Brasil vem promovendo baixa diversidade genética dos genótipos usados como enxerto e porta-enxerto, ensejando vulnerabilidade da cultura às vicissitudes bióticas como a resinose (Lasiodiplodia theobromae), principal doença do cajueiro no semiárido nordestino. Estima-se que cerca de meio milhão de mudas de cajueiro-anão-precoce sejam produzidas anualmente, sendo a grande maioria delas produzida de propágulos enxertados sobre plântulas oriundas de sementes do clone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…For the L. theobromae-inoculated plants, however, significant and continuous reductions in the F v /F m ratios over time demonstrated actual perturbations in plant metabolism, as clearly observed in both types of samples. For cashew plants, the pathogenic action of Lasiodiplodia is not fully understood, but damage to the plant might be occurring via reductions in water and nutrient transport, leading to reduced photosynthesis, which would explain the substantial decreases in the F v /F m ratios (Cardoso et al 2010). Previous determinations of the microscopic features of the colonization of cashew plants by L. theobromae (Muniz et al 2011) indicated the presence of the fungus within the xylem vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the L. theobromae-inoculated plants, however, significant and continuous reductions in the F v /F m ratios over time demonstrated actual perturbations in plant metabolism, as clearly observed in both types of samples. For cashew plants, the pathogenic action of Lasiodiplodia is not fully understood, but damage to the plant might be occurring via reductions in water and nutrient transport, leading to reduced photosynthesis, which would explain the substantial decreases in the F v /F m ratios (Cardoso et al 2010). Previous determinations of the microscopic features of the colonization of cashew plants by L. theobromae (Muniz et al 2011) indicated the presence of the fungus within the xylem vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Once infected, cashew seedlings constitute a primary inoculum for the fungus in the field and usually display no visual symptoms of infection. Therefore, the lack of an early detection method contributes to the spread of the disease (Cardoso et al 2010). Thus far, diagnosis and identification of the gummosis pathogen has been based upon the emergence of symptoms and subsequent isolation of the pathogen on agar media.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, diferentes combinações entre porta-enxertos e copa resultam em alterações fisiológicas das plantas, que podem originar melhores adaptações a diferentes condições ambientais (Paiva et al, 2008). Alguns autores evidenciam a existência de diferentes interações entre porta-enxertos e copas de cajueiro quanto à resistência às doenças (Cardoso et al, 2010), tolerância à salinidade (Carneiro et al, 2004;Ferreira-Silva et al, 2009;Sousa et al, 2011) e exigências hídricas (Oliveira et al, 2003). Ressaltese, ainda, a utilização de um número reduzido de genótipos, tanto como porta-enxerto quanto como copa, que caracteriza uma situação de vulnerabilidade genética a fatores bióticos ou abióticos que podem comprometer toda a cadeia produtiva (Melo Filho et al, 2006;Paiva et al, 2008 Os garfos utilizados foram obtidos dos jardins clonais de cajueiro localizados no CEP, que apresentavam aproximadamente 10 cm de comprimento e 5 mm de diâmetro, com gema terminal em início de brotação, conforme Cavalcanti Júnior (2005).…”
Section: Methodsunclassified
“…Initial symptoms appear as a wound in the trunk that evolves into a gum exudative canker and, soon after, the yellowing of the leaves and plant decay. Protective measures are not available, with treatments remaining inefficient (Cardoso et al, 2010). In addition to cashew plants, L. theobromae negatively impacts several different crop cultures, including avocado (Persea americana Mill.…”
Section: Introductionmentioning
confidence: 99%